Math, asked by shrutigupta18, 10 months ago

ans this question urgent​

Attachments:

Answers

Answered by anupama1568
0

Answer:

3x -  \frac{y + 7}{11}  + 2 = 10 \\ 2y +  \frac{x + 11}{7}  = 10 \\  \\ 3x -  \frac{y + 7}{11}  + 2 = 10 \\ 3x -  \frac{7y}{11}  + 2 = 10 \\ 3x - 77y + 2 = 10 \\ 74xy + 2 = 10 \\ xy = 10 + 2 - 74 \\ xy = 12 - 74 \\ xy =  - 62 \\  \\ 2y +   \frac{x + 11}{7}  = 10 \\ 2y +  \frac{11x}{7}  = 10 \\ 2y + 77x = 10 \\ 79xy = 10 \\ xy = 79 - 10 \\ xy = 69

I hope it help you if it correct follow me and like the answer and mark me brainlest

Similar questions